2013
DOI: 10.1016/j.critrevonc.2012.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Prospective of colon cancer treatments and scope for combinatorial approach to enhanced cancer cell apoptosis

Abstract: Colorectal cancer is the leading cause of cancer-related mortality in the western world. It is also the third most common cancer diagnosed in both men and women in the United States with a recent estimate for new cases of colorectal cancer in the year 2012 being around 103,170. Various risk factors for colorectal cancer include life-style, diet, age, personal and family history, and racial and ethnic background. While a few cancers are certainly preventable but this does not hold true for colon cancer as it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
117
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 126 publications
1
117
0
3
Order By: Relevance
“…Gastrointestinal (GI) tract is the first organ that interacts with dietary components and luminal microbiota both of which are known to regulate diabesity (16,17,23,24). Our previous works show multiple roles of mucosal Jak3 in the regulation of intestinal functions including mucosal cytoskeletal remodeling (25), intestinal restitution (26), mucosal homeostasis and differentiation (27), mucosal barrier functions (28), trans-molecular regulation of Jak3 activation, and assessment of Jak3-directed therapies (29,30). Recently, we reported that loss of colonic mucosal expression of Jak3 not only led to reduced mucin expression and development of intestinal CLGI in mice but they also had tendency of gaining body weight, a phenotype consistent with human metabolic syndrome (28).…”
mentioning
confidence: 99%
“…Gastrointestinal (GI) tract is the first organ that interacts with dietary components and luminal microbiota both of which are known to regulate diabesity (16,17,23,24). Our previous works show multiple roles of mucosal Jak3 in the regulation of intestinal functions including mucosal cytoskeletal remodeling (25), intestinal restitution (26), mucosal homeostasis and differentiation (27), mucosal barrier functions (28), trans-molecular regulation of Jak3 activation, and assessment of Jak3-directed therapies (29,30). Recently, we reported that loss of colonic mucosal expression of Jak3 not only led to reduced mucin expression and development of intestinal CLGI in mice but they also had tendency of gaining body weight, a phenotype consistent with human metabolic syndrome (28).…”
mentioning
confidence: 99%
“…Chemotherapy is used in combination with surgery in metastatic cases and to tackle advanced stage tumours (Mishra et al 2013;Ganai 2015). The prognosis of colon cancer patients has improved to a greater extent due to advanced therapeutic approaches (Carrato 2008;Mishra et al 2013). Despite the advanced therapies, there are certain cases that are refractory emphasizing the desperate need to develop novel target therapies for such monotonous cases (Ganai 2015).…”
Section: Pracinostat In Colorectal Cancer Therapymentioning
confidence: 99%
“…Surgical removal of affected area is the principal therapy for colorectal cancer (Hind et al 1992;Mishra et al 2013;Ganai 2015). Chemotherapy is used in combination with surgery in metastatic cases and to tackle advanced stage tumours (Mishra et al 2013;Ganai 2015). The prognosis of colon cancer patients has improved to a greater extent due to advanced therapeutic approaches (Carrato 2008;Mishra et al 2013).…”
Section: Pracinostat In Colorectal Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy, radiotherapy, hormone therapy, immune therapy and surgery have shown limited success in the treatment of cancers [1]. Therefore, it is imperative to search for additional anti-cancer drugs in the treatment and management of cancers.…”
Section: Introductionmentioning
confidence: 99%